Doing Indefinite Time: Penal Confinement and the Life-Imprisoned Offender in Denmark, Finland, and Sweden - Schartmueller, Doris (The prison journal, 2019)
Penal confinement in Danish, Finnish, and Swedish prisons has become a topic of growing interest in comparative penal research. While prison sentences in these countries are characterized by reintegration, offenders serving life sentences with unknown dates of release pose particular challenges. This study involved comparing and contrasting the enforcement of life sentences in Denmark, Finland, and Sweden through comparative legal research and interviews with criminal justice practitioners. The findings suggest reintegrative efforts for life-imprisoned offenders are in theory the same as those for any other prisoner but, in practice, some implementation difficulties arise due to the indefinite character of their sentence.